2014
DOI: 10.1177/0956797614551573
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Culture Into the Study of Affect and Health

Abstract: Curhan and colleagues (2014) have correctly pointed out that culture is likely to play a critical role in understanding affect-health associations. Despite wide recognition of crosscultural variation in experienced affect, affect ideals, and other emotion-related cognitions (e.g., Markus & Kitayama, 1991;Mesquita, 2001;Tsai, 2007;Williamson et al., 2012), affect-health research rarely includes cultural variables. We take this point to heart and agree that health-related science should pay more attention to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…The picture of universality is consistent with prior research demonstrating that affect has fairly comparable effects over time on American and Chinese children's autonomous motivation during early adolescence (Pomerantz & Qin, 2014). It is also in line with findings that affect plays a comparable role in health during adulthood in a variety of countries, including the United States and China (Pressman et al, 2013(Pressman et al, , 2014. However, other studies point to the possibility that the role of affect differs in the West and East Asia.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The picture of universality is consistent with prior research demonstrating that affect has fairly comparable effects over time on American and Chinese children's autonomous motivation during early adolescence (Pomerantz & Qin, 2014). It is also in line with findings that affect plays a comparable role in health during adulthood in a variety of countries, including the United States and China (Pressman et al, 2013(Pressman et al, , 2014. However, other studies point to the possibility that the role of affect differs in the West and East Asia.…”
Section: Discussionsupporting
confidence: 89%
“…However, Pomerantz and Qin (2014) found that children's negative affect predicted dampened autonomous motivation in school over time during early adolescence similarly in the United States and China, with positive affect predicting heightened autonomous motivation only in China. Research has yielded mixed findings as to whether the effects of affect on health vary among adults in the West and East Asia, leading to debate over the issue (e.g., Curhan et al, 2014;Pressman, Gallagher, & Lopez, 2013;Pressman, Gallagher, Lopez, & Campos, 2014). In terms of spe-This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: The Role Of Affect In Self-conceptions In the West And East ...mentioning
confidence: 99%
“…Stigma leads to avoidance behaviors including resistance to seeking information about health, a reluctance to disclose personal information to social networks, and caution about seeking treatment and adhering to treatment protocols [14, 15]. Negative feelings about oneself and associated stigma are associated with poorer health outcomes [17]. Asian fatalism might provide another barrier to seeking medical care including vaccination, testing and treatment [15], since life may be believed to be unpredictable and that people have limited control over their own destiny.…”
Section: Discussionmentioning
confidence: 99%
“…Emotions are central to relationships (e.g., Keltner & Haidt, 2001;Shiota, Campos, Keltner, & Hertenstein, 2004) and have long been recognized as a rich space of sociocultural variation (Mesquita, Frijda, & Scherer, 1997). Recent studies highlight the importance of this topic for health (e.g., Curhan et al, 2014;Pressman, Gallagher, Lopez, & Campos, 2014;Soto et al, 2011). The few studies that have examined cultural variation in emotion within relationship Culture,Relationships,and Health 669 settings suggest that this is an important area for future research.…”
Section: Emotionsmentioning
confidence: 99%